Enhanced Detection of Short‐Chain Fatty Acids Using Gas Chromatography Mass Spectrometry. Issue 6 (24th June 2021) - Gu, Haiwei; Jasbi, Paniz; Patterson, Jeffrey; Jin, Yan
Abstract: Short‐chain fatty acids (SCFAs) are produced mainly by intestinal microbiota and play an important role in many host biological processes such as immune system development, glucose and energy homeostasis, and regulation of immune response and inflammation. In addition, they participate in the regulation of anorectic hormones, which have a role in appetite control, tumor suppression, and regulating the central and peripheral nervous systems. As such, there is great interest in monitoring levels of SCFAs in various biological samples. Due to the highly hydrophilic and volatile characteristics of SCFAs, optimizing extraction and sample preparation procedures is often a central component to further improve SCFA quantification. Here, we describe a rapid and highly sensitive analytical method for measuring SCFAs in human serum and feces. Briefly, SCFAs are protected by adding sodium hydroxide, followed by a one‐step extraction (pH > 7). Then, SCFAs are quantified by gas chromatography coupled to mass spectrometry (GC‐MS) after derivatization with N ‐ tert ‐butyldimethylsilyl‐ N ‐methyltrifluoroacetamide (MTBSTFA). This method demonstrates excellent sensitivity, linearity, and derivatization efficiency for simultaneous determination of 14 different SCFAs. Further, this validated method can be successfully applied to quantify SCFAs in micro‐scale biological samples. In summary, we describe efficient and advanced sample preparation and detection procedures that are critically needed for monitoring SCFA concentrations in human biological samples. © 2021 Wiley Periodicals LLC. Basic Protocol : SCFA extraction and detection from fecal and serum samples with gas chromatography−mass spectrometry